Carbon particles (CPs) derived from dry milled biochar - Md Yusof, Juraina; Mohd Salleh, Mohamad Amran; Abdul Rashid, Suraya; Ismail, Ismayadi; Mat Nong, Mohd Ali (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents the characterization of carbon particles (CPs) derived from dry milled biochar originated from kenaf, coconut and bamboo. The biochars were processed in a dry milling mechanical alloying equipment using two hardened steel vials set and steel balls as a milling media at room temperature. Characterization of the CPs after 12 hours milling portrays significant changes of the materials of its size and structural transformations as observed from the Raman spectrum. The material size is further reduced with a function of time due to the shear forces introduced during milling. It was found that CPs from coconut biochar has a total of 39 m2/g Brunauer–Emmett–Teller surface area which is higher than the surface area of kenaf and bamboo after milling.